Peripheral role of glutamate in orofacial pain - Liu, Jinyue; Jia, Shilin; Huang, Fang; He, Hongwen; Fan, Wenguo (Frontiers in Neuroscience, 2022)
Glutamate is the principal excitatory neurotransmitter in the central nervous system. In the periphery, glutamate acts as a transmitter and involves in signaling and processing of the sensory input. Glutamate acts at several types of receptors and also interacts with other transmitters/mediators under various physiological and pathophysiological conditions including chronic pain. The increasing amount of evidence suggests that glutamate may play a role through multiple mechanisms in orofacial pain processing. Here, we review the current understanding of how peripheral glutamate mediates orofacial pain, how glutamate is regulated in the periphery and how these findings are translated into therapies for pain conditions.